Linux on the Mainframe - Eilert, John; Eisenhaendler, Maria; Matthaeus, Dorothea; Salm, Ingolf (Prentice Hall PTR, 2003)
Annotation
Keywords: Application software -- Development; Unix (Computer Operating System); Operating Systems (Computers); Computers; Operating Systems; Unix; Computers; Operating Systems; General; Logiciels d'application; Développement; Application software; Development